njunctions in class action for the protection of thetransgenerational right to environment “water resources» (2014)
This article studies the injunctions as a means of protecting the right to a healthy environment in compliance with articles 79 and 80 of the Constitution of Colombia of 1991. Specifically refers to the protection of water resources through the Class Action (Article 88 C.C.) and regulated by Law 472 of 1998 as a mechanism to protect collective and diffuse rights and interests related to healthy environment. Furthermore, it is determined the importance of the injunctions for the protection of water resources through the interpretation and application of judges in class actions under the precautionary principle according to which the decision of the judges should be based on ensuring transgenerational rights to a healthy environment for future generations. Also Colombian laws on water resources are compiled, specifically those in the ecosystem of wasteland, where are born the watersheds of this country, which are the subject of study by the importance for the different disciplines for their social impact. Concluding with a study on the importance of the constitutional safeguard and protection of transgenerational rights through injunctions applied temporarily when during the legal action imminent harm may be caused.